CHANGE OF MAINTENANCE OF DRY SUBSTANCES AND STARCH IN TUBERS OF POTATO IN DEPENDENCE ON TERMS OF TILL - V. K. Serderov; T. G. Chanbabaev; D. V. Serderova (Овощи России, 2019)
Potatoes is the most important food crop, one of the main crops grown throughout the world. A way to improve the profitability of the potato industry is processing. The processing production requires special varieties of potatoes. Tests were carried out by the department of vegetable breeding «Agrarian scientific center of republic of Dagestan» in 2017-2018 with the purpose of study the effect of soil-climatic conditions of Dagestan highlands on dry matter and starch content in potato tubers for production of processed potato products. Processing of potatoes is one of the methods to increase profitability of industry. One of the quality indexes of the use of potato varieties for their processing is high level of dry matter and starch. As a result of the research, the following varieties were identified: high-yielding are Impala, Irbit, Zhukovsky Ranniy, Manifesto, Matushka, Nevsky, Primabella, Rosara, Silvana, Spiridon and Udacha; high dry matter content are Alena, Vektor, Dzhokonda, Desiree, Matushka, Nart, Primabella and Rossi; high in starch: Desiree - 23%, Vector and Primabella - 22.2% each. The results of the present investigation revealed that climate of the mountainous areas of Dagestan republic promotes the increase of dry matter and starch content in potato tubers by 3-4%.